Effectiveness of Streptocycline Spray Schedules on the Bacterial Blight Intensity and Yield of Clusterbean - Lodha, Satish; Ram, K Anantha (Annals of Arid Zone, 2016)
Thirteen schedules of sterptocycline were attempted to record their effectiveness against bacterial blight [Xa1llhomollas campeslris Pv. cyamopsidis (Patel et al.) Dye] of c1usterbean [Cyamopsis Icrragolloloba(L.) Taub.]. Seed treatment (250 ppm) followed by two sprays of streptocycline (100 ppm) at 5 th and 7th week after planting significantly reduced the blight intensity and increased the grain yield. The combination provided an additional seed yield of 1.52 kg per rupee of additional investment on the antibiotic.